Analysis of Decisions Declaring a Claim Inadmissible (Niet Ontvankelijk Verklaard) in Civil Cases: (A Case Study at the Blambangan Umpu District Court) - Arif Adi Seftian; Titin Purwaningsih; Daffa Hanif Hilmi; Selsa Hadilla Azhara; Fiqri Alfrica Arfa; Mustika Hayati (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The decision of inadmissible claims (Niet Ontvankelijk Verklaard/NO) is a common phenomenon in civil litigation practice and reflects the importance of fulfilling formal requirements in drafting a lawsuit. This study aims to analyze judges’ legal reasoning and identify the formal factors causing claims to be declared inadmissible at Pengadilan Negeri Blambangan Umpu. This research employs a qualitative approach with a case study method through document analysis, interviews, and literature review. The results show that the main causes of Niet Ontvankelijk Verklaard decisions include obscure claims (obscuur libel), incomplete parties (plurium litis consortium), inconsistency between posita and petitum, formal defects in power of attorney, and unclear object of dispute. Among these factors, obscuur libel is the most dominant, indicating weak legal construction of claims. Judges’ considerations in issuing Niet Ontvankelijk Verklaard decisions reflect the application of prudential principles to maintain legal order and certainty. However, this condition also reveals a tension between procedural justice and access to justice. Therefore, improving the quality of claim drafting and public legal literacy is essential.